Crown discoloration promoted by materials used in regenerative endodontic procedures and effect of dental bleaching: spectrophotometric analysis - Luciane Geanini Pena dos SANTOS; Wilson Tadeu FELIPPE; Beatriz Dulcineia Mendes de SOUZA; Andrea Cristina KONRATH; Mabel Mariela Rodríguez CORDEIRO; Mara Cristina Santos FELIPPE
Abstract Regenerative endodontic procedure (REP) has been proposed as a new approach to treat immature permanent teeth. However, materials used in REP for root canal disinfection or cervical sealing may induce tooth discoloration. Objectives To assess tooth crown's color after intracanal treatment with triple antibiotic paste (TAP) or calcium hydroxide (CH); cervical sealing with glass ionomer cement (GIC) or mineral trioxide aggregate (MTA); and bleaching with carbamide peroxide. Material and Methods After pulp removal and color spectrophotometer measurement, 50 bovine incisors were divided into 4 experimental groups and one control (untreated). Experiments were performed in phases (Ph). Ph1: TAP (ciprofloxacin, metronidazole, minocycline), TAPM (ciprofloxacin, metronidazole, amoxicillin), DAP (ciprofloxacin, metronidazole), or CH treatment groups. After 1 and 3 days (d); 1, 2, 3 weeks (w); and 1, 2, 3 and 4 months (m), color was measured and medications were removed. Ph2: GIC or MTA cervical sealing, each using half of the specimens from each group. Color was assessed after 1d, 3d; 1w, 2w, 3w; 1m and 2m. Ph3: Two bleaching sessions, each followed by color measurement. Data were analyzed with ANOVA and post-hoc Holm-Sidak method. Results Ph1: Specimens of TAP group presented higher color alteration (ΔE) mean than those of TAPM group. No significant difference was found among TAP or TAPM and CH, DAP or Control groups. Ph2: cervical sealing materials showed no influence on color alteration. Ph3: Different ΔE means (from different groups), prior to bleaching, became equivalent after one bleaching session. Conclusions TAP induces higher color alteration than TAPM; color alteration increases over time; cervical sealing material has no influence on color alteration; and, dental bleaching was able to recover, at least partially, the tooth crown's color.